دلالات اللام في الصحيفة السجّاديّة Connotations Of " L " Letter Lam in " AL- Sahif AL- Sajjadiyy " - Hussein Jaafer Aubeid حسين جعفر عبيد; Emad Fahdil Abed عماد فاضل عبد (Journal Of Babylon Center For Humanities Studies, 2019)
The linguists and grammarians have been alerted to the importance of these letters and their effect in linking the words to each other and changing their meanings to collect the multiple meanings. Therefore, special attention has been given to them in the attempts of many of them to set limits for this term. And on the other hand to determine the meanings of those letters and to show their secrets and methods of use. And that one of the most important of these letters (the non), has put some scholars of the Arabic literature of his own; to explain the meanings and sections and conditions of work, while others devote chapters or chapters in their books And the dispute occurred in the origin of its meanings, so went to the group that the origin of the meaning is the king, and others went to the merit is the origin of the meanings, and some of them felt that the meaning of jurisdiction to give up the king and merit. The grammarians differed in permitting the deletion of the infallible woman, while keeping her work and saying in it four: it is permissible to do so in particular, and this is not permissible at all, and it is permissible to do so after the statement of Amri and his passport after the saying. حظيت حروف الجر ومعانيها باهتمام الدارسين قديمًا وحديثًا، وقد تنبه اللغويون والنحويون على أهمية هذه الحروف وأثرها في ربط الكلمات بعضها ببعض، وتغيير دلالاتها لتحصيل المعاني المتعددة؛ لذا أولوها عناية خاصة تمثلت من جهة في محاولات الكثير منهم وضع حدود لهذا المصطلح بدءً بسيبويه وانتهاءً بالمتأخرين. ومن جهة أخرى تحديد معاني تلك الحروف وبيان أسرارها وأساليب استخدامها. وإنَّ واحدًا من أهم هذه الحروف (اللام)، فقد وضع بعض علماء العربية مؤلفات خاصة له؛ لبيان معانيه وأقسامه وشروط عمله، في حين افرد آخرون فصولًا أو ابوابًا في كتبهم ووقع الخلاف في أصل معانيها، فذهبت جماعة إلى أنّ أصل معانيها هو الملك، وذهب آخرون إلى أنّ الاستحقاق هو أصل معانيها، ومنهم من رأى أنّ معنى الاختصاص يغني عن الملك والاستحقاق. واختلف النحويون في جواز حذف اللام الجازمة مع إبقاء عملها والأقوال في ذلك أربعة: جواز ذلك في الشعر خاصة، وعدم جواز ذلك مطلقًا، وجوازه بعد قول أمري، وجوازه بعد القول.